Effects of Herbal Forte Rice as Replacement of Carbohydrate to Insulin Resistance in Patients with Type 2 Diabetes in Sumbersari Health Center Jember - Dina Faizatur Rahmah; Ancah Caesarina Novi Marchianti; Rini Riyanti (Faculty of Medicine, University of Jember, 2017)
The population of type 2 diabetes mellitus sufferer continuously increases due to the increase of insulin resistance characterised by the rise of the secretion insulin. Insulin resistance is affected by several factors such as the lack of physical activity, obesity, and unhealthy diet. One of the characteristics of the unhealthy diet is the high consumption of carbohydrates.Whereas Indonesian prefers to have carbohydrate sources from food which has high glycemic index such as rice so thatit makes the glucose in the blood increased rapidly. This condition causes more and faster insulin secretion and can affect insulin resistance. The purpose of this study is to know the effectiveness of herbal forte rice as a substitute of the main carbohydrate in the state of hyperinsulinemia suffered by 15 patients of type 2 diabetes mellitus in Puskesmas (community health center) Sumbersari Jember. This study is a clinical trial with a quasi experimental method and crossover design. In this study, the sample is interviewed by characteristics (age, gender) and the early consumption patterns using 24-hour food recall three times at different times. Samples acted as a control group once the experimental group. The control group did not receive any treatment, while the experimental group received the herbal forte rice as much as 100 grams for 7 consecutive days in the morning (at 06.30 am). After washing out period for 9 days, experimental group switched into control group. At the end of the period (7 days), data of fasting blood glucose and fasting insulin were collected then counted by HOMA-IR formula. The result of the study based on the paired t test p=0.001 in comparison to the state of the control and experimental group. The conclusion of this study is there is a changing state of insulin resistance with the replacement of food based on glycemic index.